Hadis Terbitnya Bintang Ṡurayyā Dalam Musnad Imam Ahmad Bin Hanbal (Studi Sanad Dan Matan Hadis) - Hurairah, Abi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Starting from the Covid-19 virus outbreak that never went away, most of the parties felt suffering. Until it is natural that all groups really hope that this epidemic will disappear soon. As was the excitement of the news circulating through the twitter account of one of the residents who argued that this covid-19 outbreak would end soon when a star rose in the morning. This is based on information from the hadith of the Prophet صلى الله عليه وسلم in the history of Imam Ahmad bin Hanbal which states this. But in reality until now the Covid-19 outbreak is still there. The existence of this incident is feared to raise suspicions among the public that not all the words of the prophet are true (lies). With this, the researcher focuses on two problem formulations. First, how is the quality of the sanad and matan of the hadith regarding the publication of the urayya star as a sign of the end of the plague, secondly, how is the content of the hadith. This study uses the takhrij wa dirāsah al-asanid method in the sanad, while the matan uses the Syarhu al-Had method. The approach used is historical with the type of library research. The data collection methods used are takhrij, iʻtibar and Syarhu al-ḥadīṡ. The results of this study The Hadith about the rising of the urayya star as a sign of the end of this plague is classified as asan Garib. If you look at the sanad, this hadith is classified as mutta'il. However, in terms of quality, this hadith is considered asan because there are narrators whose credibility does not meet the requirements of aḥīḥ hadith, namely Isl bin Sufyān al-Tamīmī al-Yarbūʻī, he is considered aʻīf. Because it only came from a friend of Ab Hurairah and then only pivoted to Imam Ahmad bin Hanbal, this hadith is considered garb and includes absolute garb. While the matan is not aḥīḥ because it does not meet the criteria for aḥīḥ-matan. This deficiency is contrary to the arguments of the Qur'an and common sense. The content of this hadith is an explanation or information of the Prophet regarding the time of the disappearance of pests which is marked by the rising of the star (Ṡurayyā) in the morning. But what must be underlined is that the word al-ʻĀhatu here is not the Covid-19 (corona) outbreak or the plague in general, but disputes and disputes between people at that time regarding the sale and purchase of fruits that were defective or damaged because it was not yet timed. to be harvested. The Prophet then forbade this activity and made the publication of the urayya star as a benchmark for the resumption of buying and selling. This is because when the Ṡurayya star rises, according to custom in the Hijaz lands, it is the beginning of the harvest season, which in the end makes the sale and purchase dispute averted (lost/raised).